About the M|G|∞ Queue Approximation by a Markov Renewall Process - Ferreira, M. A. M. (EasyChair Preprint no. 11516, 2025)
Some M|G|inf queue systems interesting quantities values approximations, obtained through the consideration of an adequate Markov renewal process, are presented, and discussed.